Targeted Next-Generation Resequencing of Gene Identifies Novel Multiple Variants Pattern in Severe Hereditary Factor V Deficiency - Piotr K. Janicki; Sonia Vaida; Hamid A. B. AL-Mondhiry (Case Reports in Genetics)
The present study investigated the genetic defects underlying severe Factor V deficiency in a 26-year-old Columbian (South America) female and her immediate family (both parents and newborn child) by next generation sequencing (NGS) of the entire gene locus. Five mutations in the coding sequence of , including three missense single-nucleotide variants (R2102H, R513K, D107H) and two synonymous variants (A135A , S184S), were identified and confirmed by the Sanger sequencing in the investigated proband (homozygote for all detected mutations), her parents, and her newborn child (all heterozygotic carriers for identified mutations). Each of the three missense variants was previously associated with separate phenotypes, including Factor V deficiency (R2102H), thrombosis (R513K) and frequent miscarriages (D107H). In addition, at least 75 additional single-nucleotide variants (including six novels) were identified in untranslated region of .